Performance Evaluation of Selected Cement Companies in India through Value Added Statements - Rathod Anjali K; Dadhaniya Abhisha C (Celebes Scholar pg, 2022)
Directors have turned their consideration to the way of increasing the value of their companies. And for that one of the major goals for higher authority of financial management is to do maximum utilization of the capital employed. This study gives an importance to the performance evaluation through value added statements of selected cement companies. This study is done to prepare and analyze value added statements and also compare the value-added ratios of selected cement companies in India. This secondary data-based study selects two cement companies as samples by using simple random sampling method of probability sampling from NSE and BSE listed cement companies. In this study ratio analysis as an accounting tool is used in which five value added ratios are selected and T-test technique of parametric test as statistical tool is used to identify the difference between samples mean. As per the result of the value-added statements it is found that value created by Ultratech Cement Ltd. was higher than Ambuja Cement Ltd. during this study period. As per the result of T test it can be said that the performance of both the companies are equal in performing ratios excluding Government share to net value added ratio and Capital provider to net value added ratio. The overall conclusion can be made on the basis of value-added ratios that during these five years the performance of Ultratech Cement Ltd. was better than Ambuja Cement Ltd.